UCSF ChimeraX: Tools for structure building and analysis - Meng, Elaine C.; Goddard, Thomas D.; Pettersen, Eric F.; Couch, Greg S.; Pearson, Zach J.; Morris, John H.; Ferrin, Thomas E. (Protein science, 2023)
Advances in computational tools for atomic model building are leading to accurate models of large molecular assemblies seen in electron microscopy, often at challenging resolutions of 3–4 Å. We describe new methods in the UCSF ChimeraX molecular modeling package that take advantage of machine‐learning structure predictions, provide likelihood‐based fitting in maps, and compute per‐residue scores to identify modeling errors. Additional model‐building tools assist analysis of mutations, post‐translational modifications, and interactions with ligands. We present the latest ChimeraX model‐building capabilities, including several community‐developed extensions. ChimeraX is available free of charge for noncommercial use at https://www.rbvi.ucsf.edu/chimerax.